BS ISO/IEC 10192-4-1. Information technology. Home Electronic System (HES) Interfaces. Part 4-1. Common user interface and cluster-to-cluster interface to support interworking among home cluster systems. Architecture (10th July 2020) - British Standards Institution,
No abstract available